A Renally Clearable Activatable Polymeric Nanoprobe for Early Detection of Hepatic Ischemia‐Reperfusion Injury. Issue 24 (14th May 2022) - Huang, Jiaguo; Xian, Shiyun; Liu, Yi; Chen, Xiaona; Pu, Kanyi; Wang, Hangxiang
Abstract: Although hepatic ischemia‐reperfusion injury (IRI) represents a major complication in many clinical settings, it remains a diagnostic dilemma due to its reliance on insensitive assays or invasive biopsy. The development of an activatable polymeric nanoprobe (APNSO ) for real‐time in vivo near‐infrared fluorescence (NIRF) imaging and urinalysis of hepatic IRI is reported here. APNSO has a backbone comprising renally clearable fluorophore fragments and self‐immolative structural units. In the presence of an oxidative stress biomarker (superoxide anion, O2 − ) during hepatic IRI, APNSO can be fluorescently activated for in vivo NIRF imaging and depolymerized to release renally clearable fluorophores for urinalysis. By virtue of its high hepatic accumulation, sensitive response toward O2 −, and effective release of renally clearable fluorophores, APNSO ‐based imaging and urinalysis detect hepatic IRI at least 7 h earlier than typical clinical assays in a mouse model. This study not only provides new opportunities for noninvasive diagnosis of hepatic IRI, but also reveals guidelines for the development of optical nanosensors for early urinalysis. Abstract : An activatable polymeric nanoprobe that possesses superoxide‐anion‐triggered renal clearance and near‐infrared fluorescence response is developed. The nanoprobe efficiently accumulates in the liver, and sensitively reacts with upregulated superoxide anions to undergo in situ depolymerization, and effectively releases a fluorescent artificial urinary biomarker for real‐time imaging and urinalysis of hepatic ischemia‐reperfusion injury at the early stage.